Dye sensitized photoelectrolysis cells. (23rd May 2019) - Yun, Sining; Vlachopoulos, Nick; Qurashi, Ahsanulhaq; Ahmad, Shahzada; Hagfeldt, Anders
Abstract : This review from theory to practice discusses the principles and designs of dye-sensitized semiconductor photoelectrodes for water splitting and electrolysis reactions. Abstract : To advance the progress of photoelectrolysis, various promising devices integrated with p- and n-type photocatalysts and dye sensitized photoelectrodes have been systematically studied. This review discusses, from theory to practice, an integration strategy for state-of-the-art dye sensitized solar cells (DSSCs) with potential p- and n-type photo-electrocatalysts or directly with dye sensitized photoanodes and cathodes for hydrogen and oxygen production through water splitting. Thorough insight into the theoretical approach which systematically drives the photoelectrolysis reaction directly or in a coupled mode, with diverse configurations of DSSCs and other photovoltaic (PV) cells, is crucial to understand the underlying fundamental concepts and elucidate trends in such reactions, and will serve as a guide to design new electrocatalysts and their integration with new PV devices, while simultaneously underlining major gaps that are required to address the challenges. Likewise, challenges, opportunities and frontiers in tandem and hybrid perovskite electrolysis processes are also discoursed in the present tutorial review. We illustrate our analysis by encompassing these integrated systems to photo-electrolysis, artificial photosynthesis such as CO2 conversion into value-added chemical reduction-products, where advancements in new catalysts and solution-processed inexpensive PV devices can certainly enrich the overall performance of the renewable production of solar fuels, including solar driven carbonaceous fuels.